2018
DOI: 10.12681/jhvms.15487
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 levels in sow milk

Abstract: ABSTRACT. Aflatoxins (AFs) are one of the most known and investigated group of mycotoxins, which can be found as contaminants in different types of food and feed. Animals are exposed to AFs mainly through the consumption of contaminated feed, particularly products of plant origin. Among AFs, aflatoxin M1 (AFM1) is the monohydroxylated derivative of AFB1 formed in the liver and excreted into the milk of lactating animals. This study encompassed the Vojvodina region of Serbia and was aimed at determining the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The observations regarding Nevertheless, high values of AFM1 can be found where controls of raw materials are less stringent. In a survey, carried out using the ELISA method, on ten farms selected because they were critical for AF occurrence in the feed or for a sow health condition, Prodanov-Radulović et al [19] observed that 97% of the milk samples collected at 3-5 days of lactation were above the limit of determination for AFM1. Furthermore, half of the farms tested presented AFM1 values above 60 ng/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations regarding Nevertheless, high values of AFM1 can be found where controls of raw materials are less stringent. In a survey, carried out using the ELISA method, on ten farms selected because they were critical for AF occurrence in the feed or for a sow health condition, Prodanov-Radulović et al [19] observed that 97% of the milk samples collected at 3-5 days of lactation were above the limit of determination for AFM1. Furthermore, half of the farms tested presented AFM1 values above 60 ng/L.…”
Section: Resultsmentioning
confidence: 99%
“…It has been verified that a transfer of aflatoxins to sow milk occurs as indicated by the recovery of AF B1 or its metabolites M1 and M2 [17,18]; however, it is much lower than that detected in cows. Nevertheless, a Serbian survey [19] has found several samples of sow milk with values two or three times higher than that of the European Union (EU) limit fixed for cow's milk destined for human consumption [16]. As for fumonisins, in the only trial carried out on sows, minimal detectable amounts of FU B1 were found in the milk during a two-week intake of FUs [20].…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic carriers of the bacterium, either those having survived the acute form of the disease or those that were subclinically infected, are an important source of infection. The severity of disease can be signifi cantly infl uenced by differences in virulence potential of different isolates and stress factors, different co-infections with other pathogens, and extrinsic factors such as poor husbandry and insuffi cient biosecurity [28,31,35,49].…”
Section: Actinobacillus Pleuropneumoniae (App)mentioning
confidence: 99%
“…It needs to be stressed that latently infected pigs can be a permanent source of reinfection in a herd. The latent infection may be reactivated by stress (transport, mixing of pigs) or due to swine feed contamination with different mycotoxins [28,31].…”
Section: Aujeszky's Disease -Pseudorabies (Ad)mentioning
confidence: 99%
See 1 more Smart Citation